ANALISIS KEBUTUHAN PENGEMBANGAN MODUL IPA TERPADU BERBASIS BLENDED LEARNING TERINTEGRASI BENCANA BANJIR - Okta Alpindo; Elfa Oprasmani (TUNAS : Jurnal Pendidikan Biologi, 2023)
This research and development will produce an integrated science module with an integrated blended learning model for flood disasters that is valid, practical and effective. Prior to development, it is necessary to analyze the problem. One part of the problem analysis is a needs analysis. This study aims to analyze the need for the development of an integrated science module based on integrated blended learning for flood disasters. The object of this research is the teacher and students who provide responses through a questionnaire. Data analysis was carried out with simple statistics, namely percentages and also qualitatively. The results of the study stated that teachers and students agreed that during the pandemic period science learning was carried out using a blended learning model. Teachers and students also agree that science learning is integrated with events in the school environment, one of which is the flood disaster. Based on the results of the study, it can be concluded that it is necessary to develop an integrated Science Module that helps the implementation of learning during the pandemic and integrates disasters that exist in the school environment.